A new structure of microwave‐driven UV lamp. Issue 3 (16th September 2020) - Zhong, Nanya; Zhu, Huacheng; Yang, Fengming; Hong, Tao; Yang, Yang; Huang, Kama
Abstract: Microwave‐driven electrodeless UV lamps are widely used in industry. However, the ultraviolet light intensity of the traditional UV lamps is non‐uniform. In this article, a novel microwave‐driven UV lamp structure for underwater sterilization is developed, which equalizes the UV light intensity of each lamp at different positions. Based on the electromagnetic theory and the Drude model, finite difference time domain algorithm is adopted to obtain the dimensions of this new structure. An experimental system is established, and four UV lamp tubes are successfully excited and intensity of UV light at 253.7 nm is tested by spectrometer. Results show that the UV radiation of each lamp is almost same. The sensitivity of the structure is analyzed by changing the microwave power and electron density of the UV lamp. It can be found that significant changes in microwave power and electron density exhibit little effect on the uniformity of light intensity. Meanwhile, the microwave power should be large enough to excite the UV lamp and electron density may affect the S11 a little. Therefore, this structure can be applied to different types of UV lamps.